Sprint Running - Goodwin, J.; Tawiah-Dodoo, J.; Waghorn, R.; Wild, J. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Sprinting, as a sport skill; in its own right, incorporates aspects of acceleration, maximal velocity capability, and capacity to sustain high running velocity for a defined period. The averaged accel- erations of elite sprinters are in the region of 7-8m/s in the first 20 m of a sprint whilst maximum velocities can reach 12.5m/s. Sprinting is also a transferable sport skill. Being che quickest over various distances is valuable in sports like rugby and football. Acceleration ability has been highlighted (Duthie, Pyne, Marsh, and Hooper, 2006). with an ability to rapidly change pace being important to evasive play. That is not to diminish the value of high maximum velocities, with many sprints taking place from rolling starts and game breaking situations occurring above 90% of individual maximum velovity (Duthie et al., 2006). Also, higher maximum velocity potential might reduce relative effort at lower absolute speeds. The development of locomotive speed, then, in its various aspects, is a common objective for many athletes and coaches.